Pengaruh Kualitas Produk dan Citra Merek terhadap Proses Keputusan Pembelian pada PD Marmara Garut - Wati Susilawati (Fakultas Ekonomi Universitas Garut, 2017)
The purpose of this study is to determine the effect of product quality and brand image on the purchasing decision process, the effect of product quality on the purchasing decision process, and the effect of brand image on the purchasing decision process. In this study the authors used descriptive and associative methods, while the respondents in this study were 96 respondents who were consumers who bought a Honda Scoopy motorcycle, with the sampling technique used was the non-probability sampling method. The data analysis technique used in this study was the validity and reliability test. Analysis of the data used in this study is descriptive analysis and multiple linear regression analysis and uses the help of Microsoft Excel and SPSS 19. The results of the analysis in this study show that H1 has an effect on product quality and brand image on the purchase decision process. the purchase decision process and H3 there is an effect of brand image on the purchase decision process.